Structural competency in pre-health and health professional learning: A scoping review. - Caiola, Courtney; Nelson, Taylor B.; Black, Kristin Z.; Calogero, Christie; Guard, Kaitlin; Haberstroh, Amanda; Corral, Irma (Journal of Interprofessional Care)
Structural competency training provides guidance to healthcare providers on recognizing and addressing structural factors leading to health inequities. To inform the evidence-based progression of structural competency curriculum development, this study was designed to map the current state of the literature on structural competency training with pre-health students, healthcare professional students, and/or healthcare professionals. We performed a scoping review and identified peer-reviewed, primary research articles assessing structural competency training interventions. The category of learners, timing of the structural competency training, types of teaching and learning activities used, instruments used to measure training outcomes, and evaluation criteria were examined. Eleven (n = 11) articles met inclusion criteria, addressing all training levels, and largely focused on medical education. Active learning strategies and researcher-developed instruments to measure training outcomes were most used. Evaluation criteria largely focused on trainees' affective reactions, utility assessments, and direct measure of the trainee learning. We suggest designing interprofessional structural competency education with an emphasis on active learning strategies and standardized training curricula. Evaluation instruments integrated at different points in the health professional learning trajectory are important for evidence-based progression in curriculum development focused on achieving structural competency.